Strategi Humas Dalam Menyampaikan Informasi Terkait Eksistensi Taman Mini Indonesia Indah (TMII) di Masa Pandemi COVID-19 - May Syarah, Maya (Jurnal Public Relations (J-PR), 2020)
The tourism sector has been affected by the COVID-19 pandemic. The implementation of Large-Scale Social Restrictions (PSBB) and the prevention of the spread of the corona virus caused the number of local and foreign tourists to experience a drastic decline. Taman Mini Indonesia Indah (TMII) is one of the tourist objects that has experienced a decrease in visitors, before the pandemic, 80,000 people came to TMII every weekend, after the pandemic the average visitor was less than 10,000 people on weekends. The purpose of this study was to determine the TMII PR strategy in conveying information related to the existence of TMII during the pandemic including how TMII faced the new normal in the tourism sector. Using a qualitative descriptive research method with interviews with key informants, the results showed several strategies taken by TMII Public Relations, including information about online tickets, enforcement of strict health protocols in accordance with government recommendations for cleanliness, health, and safety. Another strategy is to communicate well for stakeholders, namely through social media, mass media (online media) and digital. Some of TMII's activities are delivered through virtual space.